Work-Family Dynamics and Their Influence on Job Satisfaction and Turnover Intention of Female Employees - Syamsiyati; Sunaryo, Sinto (Universitas Muhammadiyah Pontianak, 2026)
This study analyzes the effect of work-family benefits, work-family conflict, and work-family enrichment on job satisfaction and turnover intention among female employees at Yayasan Al Abidin Surakarta. A quantitative cross-sectional approach was applied to 318 respondents and analyzed using PLS-SEM with SmartPLS 4.0. The findings indicate that work-family conflict negatively affects job satisfaction and positively affects turnover intention, while work-family enrichment improves job satisfaction. In addition, job satisfaction reduces turnover intention. The study implies that educational organizations should strengthen work-family balance policies to improve employee satisfaction and reduce turnover intention. Keywords: Work-Family Benefits; Work-Family Conflict; Work-Family Enrichment; Job Satisfaction; Turnover Intention; Female Employees